Primates in Burrows: A Cause for Concern? Observations From a One Health Perspective at Niokolo Koba National Park, Senegal - Cédric Vermeulen; Jérôme Vandebos; Daelemans Virginie; Simon Lhoest (Ecology and Evolution, 2025)
ABSTRACT Burrows are places where many species cross paths and potentially exchange diseases. Primates are rarely frequenting burrows. However, this brief descriptive communication shows that three species of primates in the Niokolo Koba National Park (Senegal) frequent the vicinity of burrows, with some individuals even entering them. In particular, these primates come potentially into contact with bats. We aim to draw the scientific community's attention to the fact that burrows serve as critical interaction points for various taxa, some of which are reputed to carry zoonoses. As such, these burrows should be considered as potential “One Health hotspots” to be monitored, especially when frequented by primates in contact with rangers or tourists.